Comment on Wunsch et al. The Impact of COVID-19 on the Interrelation of Physical Activity, Screen Time and Health-Related Quality of Life in Children and Adolescents in Germany: Results of the Motorik-Modul Study. Children 2021, 8, 98 - Mathilde Kersting; Hermann Kalhoff; Thomas Lücke (MDPI AG, 2021)
A recent study concerning the "Impact of COVID-19 on the Interrelation of Physical Activity, Screen Time and Health-Related Quality of Life in Children and Adolescents in Germany" was investigated by Wunsch et al. [...]